Seminar on Ceramics Technologies in the Nineties, 12 November 1992, The Pan Pacific Hotel Kuala Lumpur : [seminar] - Seminar on Ceramics Technologies in the Nineties (1992 : Kuala Lumpur); Jamin, G. P.; Scharrer, K.; SIRIM; Interscience Sdn Bhd; Rieckermann (Malaysia) Sdn. Bhd. (Kuala Lumpur : [s n], 1992)
50